Investigating the interplay of educational factors and mental health in children with orofacial clefts: A Record Linkage Study - Rammos, Alexandros; Davies, Amy; Wren, Yvonne; Lewis, Sarah J; Sharp, Gemma C; Owen, Michael J; Van den Bree, Marianne B M; Stergiakouli, Evie (International Journal of Population Data Science, 2025)
Objectives The purpose of this study is to examine the links between CL/P (Cleft Lip and/or Palate) in children, mental health, Special Education Needs (SEN)and educational outcomes. Furthermore, we aim to identify environmental causes of neurodevelopmental and mental health problems in children born with CL/P. Methods We will be linking Special Educational Needs, absence, and academic performance data from the National Pupil Database (NPD) with the Cleft Collective (CC) study, which includes 11,315 participants from 4,039 families, collected in 16 NHS cleft centres across the UK. Using multivariable regression models adjusted for NPD-linked confounders, we will analyse associations between mental health/neurodevelopmental trajectories and school-level factors (school absences and exclusions, Key Stage test scores). Results We estimate that we will request matching on approximately 3427 children from the Cleft Collective to the NPD. We will link those with questionnaires collected at recruitment (at prenatal CL/P diagnosis, at birth, or at 5 years) and at follow-ups at ages 18 months, 3, 5, 8, 10, 12 and 15 years. In addition to key outcomes (which include Key Stage 1 and 2 results) we also aim to explore secondary outcomes that might be relevant to the CC cohort (including absence and exclusion patterns). Conclusion Through this linkage we aim to foster a deeper understanding of the specific needs of children born with CL/P, to improve the validity and relevance of these findings, to ascertain causal pathways between cleft and mental health and how this relates to educational provision for this group.